2D-Shear Wave Elastography in the Evaluation of Parathyroid Lesions in Patients with Hyperparathyroidism. (6th August 2017) - Golu, Ioana; Sporea, Ioan; Moleriu, Lavinia; Tudor, Anca; Cornianu, Marioara; Vlad, Adrian; Timar, Romulus; Balas, Melania; Amzar, Daniela; Vlad, Mihaela
Abstract : Background and Aims . 2D-shear wave elastography (2D-SWE) is a relatively new elastographic technique. The aim of the present study is to determine the values of the elasticity indexes (EI) measured by 2D-SWE in parathyroid benign lesions (adenomas or hyperplasia) and to establish if this investigation is helpful for the preoperative identification of the parathyroid adenoma. Material and Methods . The study groups were represented by 22 patients with primary or tertiary hyperparathyroidism, diagnosed by specific tests, and 43 healthy controls, in whom the thyroid parenchyma was evaluated, in order to compare the EI of the thyroid tissue with those of the parathyroid lesions. Results . The mean EI measured by 2D-SWE in the parathyroid lesions was 10.2 ± 4.9 kPa, significantly lower than that of the normal thyroid parenchyma (19.5 ± 7.6 kPa; p = 0.007 ), indicating soft tissue. For a cutoff value of 12.5 kPa, the EI assessed by 2D-SWE had a sensitivity of 93% and a specificity of 86% (AUC = 0.949; p < 0.001 ) for predicting parathyroid lesions. Conclusion . A value lower than 12.5 kPa for the mean EI measured by 2D-SWE can be used to confirm that the lesion/nodule is a parathyroid adenoma.